A cross-sectional study to assess the quality of immunization services provided through the Routine Immunization program in both urban and rural areas of Dehradun - Rafique, Farhat; Yadav, Shiv Kumar; Arya, Anupama (Indian Journal of Community Health, 2025)
Background: Vaccines are considered as tugboats of preventative health. The availability of the vaccine, as well as the quality of the vaccination at the outreach session site, are critical for improving vaccination coverage and lowering the prevalence of vaccine-preventable diseases. Aims & Objectives: Evaluation of Routine Immunization services provided at outreach session sites. Methodology: The study was conducted in rural and urban field practice areas of the Government Doon Medical College, Dehradun. 32 Routine Immunization session sites (16 each from urban and rural field practice areas) were selected through the Systematic Random Sampling method, with equal representation of best and worst-performing session sites. Results: - Out of the 32 session sites monitored, only 9.37% had their due lists updated, and only 31.24% had a head-count survey completed. ASHA mobilized beneficiaries at all sessions, although AWW mobilized beneficiaries only at 22 session sites. Alternate vaccine delivery services were not functional at any session sites. Vaccines were available at all session sites, while paracetamol was only available at 65.62% of session sites, and zinc was not available at any site. Only 21.87% of the ANMs were following injection safety guidelines. In the majority of cases, the four essential messages following immunization were not delivered. Conclusion: The quality of immunization services can be improved by providing regular training to ANMs and supportive supervision. District health officials must ensure the availability of multiple logistics at the immunization Session site and the implementation of alternate vaccine delivery services